A Tobacco Cessation Intervention with Rural, Medically Underserved, Blue-collar Employees: A Quasiexperimental Study - Telisa Stewart; Margaret K. Formica; Anna M. Adachi-Mejia; Dongliang Wang; Meg Gerrard (Elsevier, 2016)
Background: The aim of this study was to increase knowledge regarding the dangers associated with tobacco use, and decrease secondhand smoke exposure and tobacco use behaviors with an antitobacco messaging campaign among rural, medically underserved, blue-collar workers. Methods: A quasiexperimental study was conducted with employees at two worksites. One worksite received the intervention, which consisted of nine different antitobacco messages. Baseline and follow-up surveys were conducted at each worksite to assess change in knowledge and behavior; the data were compared across the two worksites. Results: Two hundred twenty-two and 243 participants completed baseline and follow-up surveys at the intervention and comparison sites, respectively. A statistically significant difference was seen over time between the worksites on knowledge of the dangers of tobacco (p < 0.0001); the mean knowledge score increased at the intervention site, but remained unchanged at the comparison site. In general, nonsmokers at both worksites appeared to try to decrease exposure to secondhand smoke over the follow-up period. Repeated measures analysis indicated that there were no differences in motivation to quit (p = 0.81), interest in quitting (p = 0.40), thinking about quitting (p = 0.53), or several tobacco-use behaviors over time among smokers at the intervention and comparison worksites. There were slight increases over time in the proportion of smokers who do not allow smoking in their homes/vehicles at the intervention worksite, although not statistically significant. Conclusion: Participants at the intervention worksite increased their knowledge regarding the dangers of tobacco use and secondhand smoke exposure. Among current tobacco users, the intervention appeared to increase family rules regarding secondhand smoke exposure in their homes and vehicles.